Exploring the factors affecting behavioral intention to adopt wearable devices - Saumya Misra; Rachana Adtani; Yuvraj Singh; Simran Singh; Devanshu Thakkar (Elsevier, 2023)
The study explores factors like healthcare, fashionability, ease of use. affecting adoption of wearable devices, with the intent to contribute to the current global health research. Objective: The objective of this study is to identify the effect of different factors on behavioral intention to adopt wearable device. With regard to the intention to utilize smart wearables, we explicitly proposed a theoretical model based on the task-technology fit (TTF) model, the technology acceptance model (TAM), and external factors. Methods: Primary data was collected from 139 respondents and structural equation modeling was performed for getting insights regarding intention to adopt wearable devices. SmartPLS software was used to analyse the data. Results: The hypothesized model explains 76.9 % variance of BI. 73.5 % of PEOU and 79.3 % of PU. Task and technology characteristics explain 88.9% of TTF construct. Connectivity and health care have a significant impact on TTF. TTF model has effect on TAM model leading to Behavioral Intention to adopt smartwatch. In addition, fashionability had a significant effect on BI. However as per study results, perceived privacy did not impact BI. Conclusions: In conclusion we document that our findings are in consistency with the original TAM and TTF model. Therefore, this provides an opportunity to extend previous findings of users' adoption. From this study the reliability and validity of integrated models is also verified. Furthermore, the aspects of wearable devices such as fashionability, ease of use, connectivity and healthcare turned out to be significant in the intention to adopt wearable devices.